A competitive analysis on non-domestic commodity trade operation of bank Asia Mohakhali Branch - Taha, Israt Jahan (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.